DOI: 10.14264/uql.2016.289
|View full text |Cite
|
Sign up to set email alerts
|

Improving fire safety and asset loss control in mining: Evaluation and development of a video based fire detection system

Abstract: The overall results of this research addressed the question of how increased time for mineworkers to evacuate mines prior to the onset of untenable fire conditions is achievable. Additionally, improved asset loss control for underground mining is feasible through the successful development of Video Based Fire Detection (VBFD) in mining, as it provides more information earlier for mine fire fighters to intervene in the growth and spread of fire, therefore maintainable coal production is achievable. VBFD may als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…By utilizing color information to extract the flame region and employing the Bayes classifier to recognize dynamic fire features, the accuracy of early fire prediction in coal mines was significantly improved. Similarly, [192] also found that video-based fire detection (VBFD) is a more effective and robust approach for providing timely fire detection and warning than traditional CO detectors in typical Australian underground mines. Another study [193] treated smoke as an indicator of early fire and employed the optical flow method to predict the predominant motion direction of smoke.…”
Section: ) Fire Monitoring and Preventionmentioning
confidence: 93%
“…By utilizing color information to extract the flame region and employing the Bayes classifier to recognize dynamic fire features, the accuracy of early fire prediction in coal mines was significantly improved. Similarly, [192] also found that video-based fire detection (VBFD) is a more effective and robust approach for providing timely fire detection and warning than traditional CO detectors in typical Australian underground mines. Another study [193] treated smoke as an indicator of early fire and employed the optical flow method to predict the predominant motion direction of smoke.…”
Section: ) Fire Monitoring and Preventionmentioning
confidence: 93%